Challenging assumptions: “unveiling meritocracy’s reality in neurosurgery” - Encarnacion Ramirez, Manuel De Jesus; Peralta Baez, Ismael Antonio; Reyes Soto, Gervith; Ntalaja Mukengeshay, Jeff; tshiunza, Cherubin mpoyi; Rosario, Andreina Rosario; Vladimir Nikolaevich, Nikolenko; Nurmukhametov, Renat; Kannan, Siddarth; Simfukwe, Keith; Duchén Rodríguez, Luis Miguel; Chmutin, Gennady; et al. (Frontiers in Surgery, 2024)
Introduction Meritocracy, a concept revered as the cornerstone of fairness and equal opportunity, is critically examined in the context of neurosurgery. This article challenges the notion that success in this demanding field is solely determined by individual abilities and effort. It reveals that factors such as background, gender, and socioeconomic status significantly influence one's career trajectory. By investigating how these systemic barriers impact admissions to neurosurgical training programs and professional advancement, the paper underscores the complexity of meritocracy in neurosurgery, suggesting that the meritocratic ideal is more nuanced and influenced by external variables than commonly believed. Results Certain universities deemed elite offer a curriculum divergent from that of their counterparts in low and middle-income countries. Students at these “elite” institutions gain exposure to new technologies and research incentives, which brings us to the realm of research. Remarkably, 75% of articles originating from developed nations account for just 25% of traumatic brain injury cases. This disparity highlights a significant research imbalance, and the common refrain underscores the need to bolster research capabilities in low-income countries. For neurosurgeons in the developing world, engaging in research often becomes a luxury due to multifaceted challenges. Financial barriers, including publication costs and paywalls for accessing articles, pose significant hurdles. Comparing salaries between countries underscores the glaring divide according to “Neurosurgeon Salary” in 2024. Neurosurgeons in the United States receive a median salary of $412,000 dollars per year, compared to $13,200 dollars in Latin America, as of June 2023. Given such incongruities, the prospect of even attending conferences or workshops abroad remains difficult for neurosurgeons from developing nations. Research isn't cast aside due to a lack of interest but due to resource limitations. The present landscape demands reconsideration. Conclusion We underscore the journey towards a more inclusive and equitable future in neurosurgery as not just a goal, but a dynamic process fuelled by resilience, collaboration, and a commitment to diversity. The narrative promotes a collective endeavour to dismantle barriers and embrace innovation, emphasizing the importance of mentorship, cross-institutional collaboration, and the amplification of underrepresented voices.